Penerapan Asas Sederhana Dan Terjangkau Dalam Proses Pendaftaran Hak Atas Tanah Secara Sporadik Di Kabupaten Lombok Barat - Zaelani - (Jatiswara, 2017)
Government regulation No. 24 1997 on the land registry, in section 2 mentioned that the land registry implemented bersasarkan some of the principle of which the principle of simple and affordable. principle simple intended to the provisions of anyway and procedure can easily be conceived by the parties concerned, especially the holder of land rights. then the principle of affordable intended affordability for parties that require especially with regard needs and the ability of class of economic weak. in particular the people in the district Lombok Western, the implementation of the principle that has not been in accordance with what to expect. in peroses registration land rights through sporadic still takes a long time and cost expensive.